Utilization of waste of chicken feathers and waste of cardboard as the material of acoustic panel maker. (March 2018) - Ansarullah,; Rahim, Ramli; Kusno, Asniawaty; Baharuddin,; Jamala, Nurul
Abstract: In The existence of chicken fur is a waste of chicken slaughterhouse Which is produced daily and still not widely used. Likewise cartons everywhere we can see its being because its function is so great in all human activities In the fulfillment of the need for storage and packaging of goods for human purposes such as electronic goods, commodity, Because it has a relatively large thickness of paper. Several studies have proven that Quill and cardboard can be used for acoustic materials. This study aims to identify the potential of chicken fur and cardboard to be created as panel materials Which acts as an acoustic panel. . This study uses an experimental method by combining two materials, Including waste Quill and carton waste by performing several stages in the formation of panels, Such as the selection of chicken fur material and cardboard cleaning process, drying process, enumeration process, panel modeling process. The result of this research is acoustic panel model with size 20x20cm2 with thickness 9 and 18 mm, The study also produced a Ø9, 8 cm diameter-shaped panel model with 1.5cm, 2.5cm, and 5cm thickness for use in testing absorption coefficients using impedance tubes.